Treatment challenges of severe hematologic manifestations of SLE in early pregnancy in a limited setting: A case report - Lestari, Sella Rizkita; Awalia, Awalia (Edelweiss Applied Science and Technology, 2025)
Hematologic abnormalities are among the most common initial manifestations of systemic lupus erythematosus (SLE), primarily including anemia, thrombocytopenia, and leukopenia. Notably, pregnancy can influence SLE disease activity, and conversely, SLE is associated with adverse pregnancy outcomes. Several treatment strategies—such as high-dose corticosteroids, immunosuppressants, intravenous immunoglobulin, and splenectomy—have been proposed to manage severe hematologic manifestations during pregnancy. However, treatment remains particularly challenging in resource-limited settings. We report a case of a young woman at 12–13 weeks of gestation who presented with severe anemia and thrombocytopenia and was subsequently diagnosed with SLE. An intravenous pulse dose of methylprednisolone and a steroid-sparing agent were prescribed, resulting in improved hemoglobin levels and platelet counts, although thrombocytopenia recurred. Following a medical decision to terminate the pregnancy, an incomplete abortion occurred. An emergency uterine curettage under general anesthesia was subsequently performed despite low platelet counts. Given the resource-limited setting, this case illustrates the complexity of managing SLE with severe hematologic manifestations during early pregnancy. It underscores the importance of timely multidisciplinary care, a careful assessment of the safety of invasive procedures, and the development of clear clinical guidelines to improve maternal outcomes in similar cases.